Association Between Carbon Emission and Low Birth Weight in Mainland China. Issue 3 (23rd March 2023) - Sun, Qi; Zhang, Ya; Wang, Yuanyuan; Lu, Jianbo; Ma, Xu
Abstract : The clinical significance of this study is that the risk of low birth weight is statistically significantly increased due to carbon emission exposure. The results contribute to formulate policies of carbon emission to reduce the incidence of low birth weight. Abstract : Objective: The aim of this study is to investigate the relationship between carbon emission and low birth weight (LBW). Methods: A nested case-control study was contacted in mainland China. Multilevel logistic regression was used to estimate the effect of carbon emission on LBW. Generalized additive mixed effect model was performed to assess no-linear trend between LBW and carbon emission. Results: Carbon emission was a risk factor for LBW (odds ratio, 1.182; 95% confidence interval, 1.011–1.383). Carbon emissions from power, residence, aviation, and transport department were risk factors for LBW (all P < 0.05). Moreover, generalized additive mixed effect model has shown that the risk of LBW decreased first and then increased as carbon emissions increased. Conclusions: Our study initially found that carbon emission may be a risk factor for LBW.